Kinetic Extraction of Moringa oleifera Leaves using the Microwave Assisted-Extraction (MAE) Method - Ghina Shofiah Adibah Khoirunnisa; Reinaldi Rizky Pratama; Ditta Kharisma Yolanda Putri; Helda Wika Amini; Boy Arief Fachri (JOBC, 2024)
Moringa oleifera leaves are known for their distinctive leaf shape and offer numerous health and nutritional benefits.They are rich in vitamins, minerals, proteins, and bioactive compounds and possess antioxidant and anti-inflammatoryproperties. This study aimed to explore the extraction process, identify the presence of tannin compounds in Moringa leaves, and determine the appropriate kinetic model for the extraction of Moringa leaf extract using the Microwave-Assisted Extraction (MAE) method. The extraction was performed using 96% ethanol as the solvent and the MAEtechnique, which is known to enhance extraction efficiency. Variables such as power (150 watts), a material-to-solventratio of 1:15 (b/v), and extraction times of 2, 4, 6, 8, and 10 minutes were tested. The results indicated that the highest yield was achieved after 10 minutes, with a value of 10.25%. The extraction time was extended at most 10 minutesdue to time limitations and diminishing returns as extraction time increased. The study concluded that the second-orderkinetic model (R² = 0.9897) was the most suitable for describing the extraction of tannin compounds from Moringa leaves,outperforming the first-order model with a value closer to 1.